Hegemonía, poder popular y sentido común (2016)
The power of capital fails through again, and their representatives know it. Therefore, their defensive policies become more aggressive. If the door is ajar, you know, it will end up open... And they defend themselves; Hence their dangerousness and ferocity. These are times of civilization collapse and as such, we must understand them and reflect on them.